2018
DOI: 10.2337/dc18-0391
|View full text |Cite
|
Sign up to set email alerts
|

T1-REDEEM: A Randomized Controlled Trial to Reduce Diabetes Distress Among Adults With Type 1 Diabetes

Abstract: DD can be successfully reduced among distressed individuals with T1D with elevated HbA using both education/behavioral and emotion-focused approaches. Reductions in DD are only modestly associated with reductions in HbA. These findings point to the importance of tailoring interventions to address affective, knowledge, and cognitive skills when intervening to reduce DD and improve glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 27 publications
4
64
0
2
Order By: Relevance
“…We have found that best results are achieved when diabetes distress is targeted directly for intervention, rather than indirectly through programmes of education or lifestyle change . Although diabetes distress in most cases should, in our view, be attended to in most or all clinical encounters , there are occasions during which attention to diabetes distress may provide particularly added value.…”
Section: Options For Where In the Care Process A Diabetes Distress Inmentioning
confidence: 84%
See 2 more Smart Citations
“…We have found that best results are achieved when diabetes distress is targeted directly for intervention, rather than indirectly through programmes of education or lifestyle change . Although diabetes distress in most cases should, in our view, be attended to in most or all clinical encounters , there are occasions during which attention to diabetes distress may provide particularly added value.…”
Section: Options For Where In the Care Process A Diabetes Distress Inmentioning
confidence: 84%
“…These findings suggest that reductions in diabetes distress as a result of intervention may not, in and of themselves, lead directly to significant improvements in self‐management or glycaemic control . It may be the case that elevated diabetes distress serves as a barrier that prevents responsiveness to interventions to improve self‐management and glycaemic control: high diabetes distress constrains energy and reduces motivation to engage meaningfully in self‐care tasks . Reducing diabetes distress, however, may allow individuals with diabetes to become more responsive to programmes that target specific management or glycaemic goals.…”
Section: Information About Diabetes Distress For Use In Intervention mentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes distress comprises the emotional burdens, stresses, and worries that may result from managing T1D [67], which have been shown to decrease in adults with T1D who use CGMs [37]. Importantly, CGM use has also been shown to not worsen diabetes distress in adolescents [68].…”
Section: Biopsychosocial Factors Associated With Cgm and Insulin Pumpmentioning
confidence: 99%
“…The narratives in some way revealed the hidden story of the lengthy process of adapting to diabetes by relaying personal diabetes journeys. The limited number of psychological interventions and resources deployed in diabetes, are currently used to support people with established diabetes [5,19,20]. The narratives also showed that important psychological and social adaptive processes took place in this early phase of diabetes such as: their psychological orientation to diabetes (acceptance/ rejection, anxiety/distress); their understanding of and confidence in self-management; and how they managed diabetes in social and work situations.…”
Section: Discussionmentioning
confidence: 98%